2003
DOI: 10.1094/mpmi.2003.16.2.141
|View full text |Cite
|
Sign up to set email alerts
|

Partial Resistance of Tomato to Phytophthora infestans Is Not Dependent upon Ethylene, Jasmonic Acid, or Salicylic Acid Signaling Pathways

Abstract: We compared tomato defense responses to Phytophthora infestans in highly compatible and partially compatible interactions. The highly compatible phenotype was achieved with a tomato-specialized isolate of P. infestans, whereas the partially compatible phenotype was achieved with a nonspecialized isolate. As expected, there was induction of the hypersensitive response (HR) earlier during the partially compatible interaction. However, contrary to our expectation, pathogenesis-related (PR) gene expression was not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
42
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 47 publications
4
42
1
Order By: Relevance
“…In our experiments on P. infestans, we found results similar to Cohen. The discrepancy between Smart et al (2003) and the findings of Cohen et al (1993) and this study are difficult to resolve because none of the data is reported by Smart et al (2003). Thus, where quantitative data have been presented, jasmonate appears to be effective at reducing susceptibility of tomato to P. infestans.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…In our experiments on P. infestans, we found results similar to Cohen. The discrepancy between Smart et al (2003) and the findings of Cohen et al (1993) and this study are difficult to resolve because none of the data is reported by Smart et al (2003). Thus, where quantitative data have been presented, jasmonate appears to be effective at reducing susceptibility of tomato to P. infestans.…”
Section: Discussioncontrasting
confidence: 81%
“…In addition, Cohen et al (1993) found that induction of the jasmonate response, using methyl jasmonate, resulted in increased resistance to P. infestans, whereas Smart et al (2003) failed to find an effect of jasmonatedeficient plants on resistance to P. infestans. In our experiments on P. infestans, we found results similar to Cohen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Pr-proteins, particularly PR-1 and PR-5, are reported as important components of the defence mechanism of potato against P. infestans (Wang et al 2006). PR genes induced in this interaction have been described as "pathogen response" genes (Smart et al 2003). Indeed, van Loon et al (2006) demonstrated that, in tomato, PR-1 was able to reduce sporangia germination and germ-tube length.…”
Section: Discussionmentioning
confidence: 99%
“…Reactions of MSI-99-expressing tomato lines to Phytophthora infestans (late blight) were assessed using detached-leaflets and growth chamber and field tests as described by Legard et al (1995), Smart et al (2003), and Mayton et al (2001), respectively. The 19 lines included in the detached leaflet assays and the four lines in the growth chamber tests were the same type of plants as those used in bacterial speck and early blight tests.…”
Section: Early Blight and Late Blight Testsmentioning
confidence: 99%